YouTube as a Source of Information for Agribusiness: Audience Perspective and Content Video Analysis - CAHYANI, Desak Dwi Asthri; ARISENA, Gede Mekse Korri (Theoretical and Practical Research in Economic Fields, 2023)
Agribusiness forms the cornerstone of many economies worldwide. Access to agribusiness information is crucial, as it is a valuable resource, catering to a diverse audience, including farmers and the general public. YouTube is a prominent online platform extensively used by people to seek information about agribusiness. The videos and content uploaded on YouTube offer an in-depth comprehension and provide diverse perspectives from various angles on the discussed topics. In agriculture, visual content plays a pivotal role in elucidating intricate concepts such as farming techniques, pest and disease management, crop variety selection, and the latest advancements in agricultural technology. This research endeavors to assess the utility of YouTube as a source of information and scrutinize the content of YouTube videos in the context of agribusiness information. The results of this data analysis reveal that most viewers accessing agribusiness-related content on YouTube are notably influenced by cognitive effects. Furthermore, the study identifies affective effects, personal integration effects, and encouragement as additional factors that impact the audience's inclination to view videos about agribusiness on YouTube. The findings from this analysis underscore the significance of factors such as the number of likes, dislikes, views, reliability assessment, video quality, and completeness evaluation in establishing a substantial correlation with audience preferences and behaviors.